Software development for mobile phone application: card dedication (MCards): article / Siti Fadhilah Sobri - Sobri, Siti Fadhilah (2007)
This paper is about designing and implementing the J2ME applications. The software program is specified for mobile devices. It is best to use Java because it offers an ideal platform for developing mobile commerce applications and using Java-enabled mobile devices. This project, MCards is designed to strike a balance between portability and usability. Products from Sun Microsystems such as Forte for Java 4, Java Development Kit (JDK) and Wireless Toolkit (WTK) were used from the beginning until the end of the software development.